Life$1 (Bs big instruction book :s the almanac of indispensable information - Madigan, Carol Orsag; Elwood, Ann. (New York : Warner Books, 1995)
From adoption to zinc in your diet, basic information on over 700 topics
Includes index.
Keywords: Handbooks, vade-mecums, etc; Conduct of life -- Miscellanea -- Handbooks, manuals, etc